2021
DOI: 10.13057/biodiv/d220355
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activities of the rhizome extract of five member Zingiberaceae against Candida albicans and Trichophyton rubrum

Abstract: Abstract. Prastiyanto ME, Rohmah N, Efendi L, Arifin R, Wardoyo FA, Wilson W, Mukaromah AH, Dewi SS, Darmawati S. 2021. Antifungal activities of the rhizome extract of five member Zingiberaceae against Candida albicans and Trichophyton rubrum. Biodiversitas 22: 1509-1513. Fungal infections have now become serious health issues. One of the strategies to avoid the problems of fungal infections is by using natural product from plants that are effective against many human pathogenic fungi. The study portrayed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
(47 reference statements)
0
8
0
1
Order By: Relevance
“…Many studies on the biological properties of Alpinia officinarum indicated its antioxidant [23,24], antiviral [25,26], antibacterial [27,28], antifungal [29,30], antimicrobial [31], analgesic and anti-inflammatory effects [32,33]. Aqueous extracts have also been studied in skin problems [34], showing antiphotoaging effects [35] and in studies on the pharmacological activity and therapeutic potential of galangin in age-related diseases [36].…”
Section: Of 21mentioning
confidence: 99%
“…Many studies on the biological properties of Alpinia officinarum indicated its antioxidant [23,24], antiviral [25,26], antibacterial [27,28], antifungal [29,30], antimicrobial [31], analgesic and anti-inflammatory effects [32,33]. Aqueous extracts have also been studied in skin problems [34], showing antiphotoaging effects [35] and in studies on the pharmacological activity and therapeutic potential of galangin in age-related diseases [36].…”
Section: Of 21mentioning
confidence: 99%
“…Beberapa di antaranya meliputi penelitian yang menggunakan ekstrak kulit biji cokelat terhadap jamur Trichophyton rubrum (Hutasoit et al, 2020), ekstrak kulit buah cokelat terhadap jamur Fusarium oxysporum (Rachmawaty et al, 2018), dan ekstrak daun cokelat terhadap jamur Candida albicans (Permataningrum et al, 2019), di mana ketiga penelitian ini membuktikan bahwa bagian tanaman Theobroma cacao yang dibuat sebagai ekstrak memiliki potensi sebagai antijamur. Candida albicans dan Trichophyton rubrum merupakan jamur Gram-positif (Prastiyanto et al, 2021)sama halnya dengan M. furfur.…”
Section: Pendahuluanunclassified
“…Fungal infections in human constitute a serious problem, especially in developing countries including Indonesia. 1 Fungal infections can result in inflammation, and each fungal species has a different response mechanism to evade the host immune system. 2,3 Inflammatory diseases are major health problem worldwide and can increase morbidity and mortality rates each year.…”
Section: Introductionmentioning
confidence: 99%